Linking traits between plants and invertebrate herbivores to track functional effects of land‐use changes. (3rd June 2013) - Moretti, Marco; de, Francesco; Ibanez, Sébastien; Fontana, Simone; Pezzatti, Gianni B.; Dziock, Frank; Rixen, Christian; Lavorel, Sandra; Pakeman, Robin
Abstract Questions Ecosystem functions and underlying services are strongly influenced by multitrophic relationships, with functional traits playing a central role in structuring them. Which traits and functional metrics mediate the impact of different types of land use on ecosystem function within and across trophic levels? Methods We studied the functional relationships between plants and grasshoppers in sub‐alpine grasslands under different management regimes in the Central French Alps. We applied the theoretical multitrophic response–effect framework described by (Journal of Vegetation Science, 24, this issue) to identify key traits linking plants and grasshoppers to biomass production. The linkages between selected plant and grasshopper traits were analysed using community‐weighted mean traits (CWM) and functional diversity (FD; Rao's quadratic diversity). Results Uni‐ and multivariate models provided evidence about the relative importance of trait linkages within and across trophic levels. We showed that management affected both plant and grasshopper traits and that the interaction between them was linked to biomass production. While a number of CWM traits and FD were involved in the interaction, CWM of leaf dry matter content (LDMC) and grasshopper dry body mass (GMass) chiefly mediated the impact of management change on biomass production. Conclusions Our study suggests that both trait values of the most abundant species and functional trait variation within and across trophic levels in combination may best explain the impact of land‐use changes on ecosystem function. To improve our mechanistic understanding across trophic levels, a better knowledge of response and effect traits remains a major goal, especially for animal ecologists, while a strong collaboration among disciplines is needed to bridge the existing gaps.